Superhydrophobic cotton fabric membrane prepared by fluoropolymers and modified nano-SiO2 used for oil/water separation. Issue 50 (24th September 2021) - Hou, Chengmin; Cao, Congjun
Abstract : Cotton modified with polymer P(GMA- r -MMA)- g -PFPA and modified silica can obtain super-hydrophobic surfaces, and can be used as oil–water separation membrane for hexane, octane, kerosene, chloroform and water mixtures in batch and continuous operation. Abstract : At present, the preparation methods of oil–water separation membranes include chemical vapor deposition, electrospinning, atom transfer radical polymerization, etc. Basically, they all have issues of low recycling rate and incontinuous use. In this paper, the epoxy polymer P(GMA- r -MMA) obtained by traditional radical polymerization of glycidyl methacrylate (GMA) monomer and methacrylic acid (MMA) monomer, and pentafluoropropionic acid (PFPA) is used to modify polymer P(GMA- r -MMA) to obtain fluorine-containing epoxy polymer P(GMA- r -MMA)- g -PFPA. Secondly, fluorine-containing epoxy polymer P(GMA- r -MMA)- g -PFPA and amino-modified nano SiO2 is blended, and the cotton fabric is dip-coated to obtain a superhydrophobic surface, thereby preparing an oil–water separation membrane. By controlling the solution concentration, dipping time, drying time and other conditions, the superhydrophobic performance of the separation membrane was characterized, and the best construction conditions for the superhydrophobic surface were obtained: 0.3 mg mL −1 polymer concentration, immersion time 6 h, drying temperature 120°, and drying time 4 h, and the maximum water contact angle can reach to 150° ± 2°. Finally, the cotton fabric was modified under the best dipping conditions, and used as an oil–water separation membrane to study the oil–water separation performance of n -hexane, n -octane, kerosene, chloroform and water mixtures in batch operation and continuous operation. In batch operations, the separation efficiency can reach 99% and can achieve 5 consecutive high-efficiency separations without intermittent drying. In continuous flow operation, oil–water separation can last for more than 12 hours and the separation efficiency can reach 98%. It also has stable oil–water separation performance for oil–water emulsion.